Pengaruh Social Capital, Business Digitalization, Dan Pemanfaatan E-Marketing Terhadap Keberlanjutan Bisnis UMKM pada sektor FnB Di Kota Malang - Nafisah, Dewi Durrotun; Susyanti, Jeni; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Indonesia is one of the countries that has a fairly large number of Micro, Small and Medium Enterprises (MSMEs) in the ASEAN region. The potential for developing Micro, Small and Medium Enterprises (MSMEs) in various sectors can have a positive impact by increasing employment opportunities. One of the significant developments that occurred in Micro, Small and Medium Enterprises in Malang City came from several sectors, one of which was the Food and Beverage sector. This research aims to find out how much influence Social Capital, Business Digitalization, and the Use of E-Marketing have on the sustainability of MSME Business in Malang City using a Quantitative approach by obtaining 97 respondents using Purposive Sampling techniques with the lameshow formula and measured using a Likert scale. After the data was collected, this research used SPSS version 24 software to test the hypothesis. The results of this research show that Social Capital, Business Digitalization, and the Use of E-Marketing have a positive effect on the sustainability of MSME businesses in Malang City. Keywords: Social Capital, Business Digitalization, E-Marketing Utilization, Business Sustainability